Analysis of the Internal Morphology of Root Canals in Teeth with Molar-Incisor Hypomineralization Using Cone Beam Tomography - Maria Gabriella Correia Pontes Reis; Ragner Bello Leite; Pedro Henrique de Alencar e Silva Leite; Vânio Santos Costa; Priscylla Gonçalves Correia Leite de Marcelos; Daniela Maria Carvalho Pugliesi; Dayse Andrade Romão; Patricia Batista Lopes do Nascimento; Valdeci Elias dos Santos Júnior (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To analyze the internal morphology of root canals in hypomineralized molars and compare them with healthy teeth and different lesion discolorations using cone-beam computed tomography (CBCT). Material and Methods: CBCT scans of Nineteen teeth were collected: five hypomineralized teeth with a creamy-white color (maxilla=2; mandible=3); eight hypomineralized teeth with a brownish-yellow color (maxilla=3; mandible=5); six healthy teeth (maxilla=4; mandible=2). Parameters such as the number of canals, foramina, accessory canals, relevant distances, and linear measurements were evaluated. The Kruskal-Wallis test and descriptive analysis were performed to assess differences between the groups, with a 5% margin of error. Results: The number of major foramina was higher in hypomineralized teeth with yellow-brown discoloration in the lower arch (p=0.029) compared to the other groups. Hypomineralized teeth exhibited smaller linear measurements when compared to healthy teeth. Conclusion: Hypomineralized teeth tended to have more complex root canal systems when compared to healthy teeth. Further research should be conducted to evaluate these parameters in larger samples.